Cakupan Gabungan Beberapa Das Mikro Dan Simulasi 2D Pengaliran Air Pada Bentang Lahan Kota Kasongan Di Kabupaten Katingan: Combined Coverage of Several Micro Watersheds and 2D Simulation of Water Flowing in Kasongan City Landscape in Katingan District - Bismart Ferry Ibie; Santosa Yulianto; Sosilawaty Sosilawaty (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
In supporting a systematic and comprehensive Strategic Environmental Assessment of the detailed spatial planning (RDTR) and Zoning Regulations (PZ) of the technical documents in the City Planning Area Section (BWP). It is necessary to understand the threat of hydrometeorological disasters, especially floods and waterlogging. Therefore, it is necessary to study the hydrological boundaries and distribution of water flow. In supporting optimal urban planning, this research was carried out on the BWP RDTR of Kasongan City, Katingan Regency periods 2020-2040 which has an area of 4,639.98 Ha. The research was carried out in August-November 2022, by delineating Micro-watersheds (sub-sub-sub watersheds) in and around the Kasongan City BWP followed by carrying out 2D simulations of water flow and inundation. The results of the study show that the BWP RDTR and PZ of Kasongan City are overlaid with Micro DAS as ecological boundaries in the form of hydrological unit polygons, showing as many as 59 polygons are affected areas with an area of 10,413 Ha. The area includes the Salangaju, Salangawa, Katunen and Liting watersheds with a polygon area ranging from 1 to 617 Ha, with an average polygon area of 179.53 Ha. Thus, the ratio between the area affected and the area of BWP and PZ is 2.24%. In the Main Program Indications, there are areas that are indicated to be experiencing a threat of flooding and inundation. It is suggested, that in its implementation carefully and precisely consider areas outside the BWP, it is also necessary to pay attention to the alternatives and recommendations that have been set to avoid floods and water inundation